Validation of tacrolimus UHPLC method and its phase solubility studies with β-cyclodextrin and its derivates - Nakov, Ana Teresa Ferreira (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019